2019
DOI: 10.1029/2019ja027147
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Ion Dynamics in the Perturbed Electromagnetic Fields Near Europa

Abstract: We model the dynamics of energetic magnetospheric ions in the perturbed electromagnetic fields near Jupiter's moon Europa. The inhomogeneities in the fields near Europa are generated by the induced dipole field from the moon's subsurface ocean as well as the Alfvénic plasma interaction with its ionosphere and induced field. Inhomogeneities in Europa's ionosphere at various length scales generate substantial asymmetries in the mass loading process that further complicate the structure of the moon's electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(127 citation statements)
references
References 66 publications
(193 reference statements)
11
113
0
Order By: Relevance
“…Figures 4i and 4j show that this feature is slightly “wavy” in longitude, due to the (small) inclination of Ganymede's magnetic moment against the orientation of the magnetospheric background field during G8 (see, e.g., Figure 1 or Jia et al, 2008). Analogous “waviness” in energetic particle precipitation patterns has also been identified at Callisto (Liuzzo et al, 2019a, 2019b) as well as Europa (Breer et al, 2019).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Figures 4i and 4j show that this feature is slightly “wavy” in longitude, due to the (small) inclination of Ganymede's magnetic moment against the orientation of the magnetospheric background field during G8 (see, e.g., Figure 1 or Jia et al, 2008). Analogous “waviness” in energetic particle precipitation patterns has also been identified at Callisto (Liuzzo et al, 2019a, 2019b) as well as Europa (Breer et al, 2019).…”
Section: Resultsmentioning
confidence: 68%
“…Nevertheless, multiple studies have documented the importance of including the locally perturbed plasma environment in order to capture and accurately model spatial inhomogeneities in the precipitation of energetic ions at Ganymede (Fatemi et al, 2016;Plainaki et al, 2015;Poppe et al, 2018). Similarly, recent studies have shown the necessity of including the perturbed plasma environments of Callisto and Europa (whose interactions with the ambient plasma play an even stronger role in shaping their electromagnetic environments) to understand energetic electron and ion bombardment of these moons (Breer et al, 2019;Liuzzo et al, 2019aLiuzzo et al, , 2019b.…”
Section: 1029/2020ja028347mentioning
confidence: 99%
“…For our model of energetic ion precipitation, we track doubly charged oxygen (O 2+ ) and triply charged sulfur (S 3+ ), as these charge states are consistent with the range of values in Clark et al (2016Clark et al ( , 2020. Using these charge states also facilitates comparison between our results and those of Cassidy et al (2013) and Breer et al (2019) for Europa, Liuzzo et al (2019b) for Callisto, and Poppe et al (2018) for Ganymede. In addition, switching from an, for example, doubly charged oxygen ion to a singly charged oxygen ion of the same velocity only increases the ion gyroradius by a factor of 2, which is equivalent to increasing the energy of the doubly charged ion by a factor of 4.…”
Section: Tablementioning
confidence: 88%
“…To develop a more comprehensive picture of energetic ion precipitation that can be used for the purpose of understanding surface weathering and atmospheric genesis at Europa, the integrated effects of a full synodic rotation must first be constrained. Additionally, Breer et al (2019) explored precipitation patterns, but did not quantify actual particle fluxes.…”
mentioning
confidence: 99%
“…In this work we investigate the cause of the depletions during E26 by simulating the flux of energetic protons using a Monte Carlo particle backtracing method. Note that we refer to any kind of flux dropout as “depletion,” be it due to surface impact, charge exchange, or Galileo encountering a “forbidden region.” Particle tracing studies have been conducted at various moons, for example, at Jupiter's moons Europa (Breer et al, ; Cassidy et al, ), Ganymede (Carnielli et al, ), and Callisto (Liuzzo et al, ), at Titan (Regoli et al, ), at Earth's Moon using backtracing (Futaana et al, ), or at Mars and Phobos (Curry et al, ; Futaana et al, ). Ion depletions have been investigated using particle tracing, for example, at the Jovian moon Io and Ganymede (Poppe et al, ; Selesnick & Cohen, ) and Saturnian moons Dione, Rhea, and Titan (Kotova et al, ; Wulms et al, ).…”
Section: Introductionmentioning
confidence: 99%